Three T2 inflammatory diseases in adolescents: asthma, eosinophilic eso- phagitis, and chronic polypous rhinosinusitis (Clinical Case) - D. Sh. Macharadze; B. G. Kulumbegov (Аллергология и Иммунология в Педиатрии)
It has long been known that comorbid diseases such as chronic polypous rhinosinusitis and obesity adversely affect the pathophysiology of asthma, impair response to therapy and reduce the quality of life of patients. Identification and effective treatment of comorbidities will improve asthma control and reduce the frequency of exacerbations. There are more and more studies that indicate a close pathophysiological relationship with allergic diseases of eosinophilic esophagitis. According to the latest data in the development of allergic diseases (asthma, allergic rhinitis, atopic dermatitis, food allergy), chronic polypous rhinosinusitis, and eosinophilic esophagitis, the key is the T2 immune response (T2 inflammation) in both children and adults. Timely diagnosis of inflammatory states of T2 inflammation can help in choosing the optimal treatment for such patients. Here we describe the comorbid conditions that occur in an adolescent with controlled asthma and discuss the features of their clinical course.   The purpose of this work is to raise the awareness of practitioners about comorbid diseases — eosinophilic esophagitis and chronic polypous rhinosinusitis in children with bronchial asthma.   Each of these comorbid diseases has clear diagnostic criteria, although they are underdiagnosed by medical specialists.